Advances in selenium-containing brown rice protein: structural characteristics, functional modification, and applications - Shu Li; Xinjie Shang; Yaxin Wu; Yumeng Wang; Shiyu Lin; Zexu Li; Zhaohui Xu; Yixuan Li; Yao Tang; Rui Yang (Food Hydrocolloids, 2026)

The influence of replacing soybean meal with corn gluten meal on the digestive and absorptive capacity and amino acid metabolism of sub-adult grass carp (Ctenopharyngodon idella) - Yan Liu; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Wen-Jie Tang; Cheng-Bo Zhong; Pei Wu (Aquaculture, 2026)

Schizantherin B alleviates cisplatin-induced ototoxicity and does not interfere cisplatin-based chemotherapy in a breast cancer model - Zirui Zhao; Lei Han; Zhijiao Xu; Benyu Nan; Honghai Tang; Dingding Dong; Zhen Zen; Ziwen Gao; Cheng Ye; Xinsheng Huang; Jianning Zhang; Geng-Lin Li; et al. (Archives of Toxicology, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Mechanisms underlying the modification of corn starch granules by raw starch-degrading amylase with substrate-targeting specificity - Lingli Zhong; Wenming Chang; Kai Yang; Songchen Jiang; Jin Lin; Yifei Shu; Yukun Zhong; Zehao Tang; Xianfeng Ye; Yanling Ji; Lei Zhang; Yan Huang; et al. (Carbohydrate Polymers, 2026)

Uncovering hidden β-adrenergic agonist exposure from meat consumption through nationally representative human biomonitoring in Taiwan - Ho-Tang Liao; Tzu-Hsuan Peng; Chien-Jen Wang; Jing-Fang Hsu; Ching-Chun Lin; Wen-Harn Pan; Shu-Lih Chia; Pau-Chung Chen (International Journal of Hygiene and Environmental Health, 2026)

Multi-level design of a chitosan-based membrane: from sisal fiber reinforcement to surface micropatterning and hybrid hap for enhanced bone regeneration - Shuo Tang; Rui Lin; Yuqing Wang; Xinyuan Feng; Fang Shi; Yupeng Guo; Shu Huang; Xiang Hu; Liuyun Jiang (Carbohydrate Polymers, 2026)

Osteopontin as an emerging multifunctional food ingredient: recent advancements, production, applications, and challenges - Shiyu Lin; Xiuxiu Teng; Xinjie Shang; Shu Li; Jingjing Xu; Yao Tang; Rui Yang (Critical Reviews in Food Science and Nutrition, 2026)

Synergistically enhanced nanofiber aerogels by directional freeze-drying and multiple hydrogen bond cross-linking for high-performance piezoresistive sensor - Xiao Su; Yufeng Bao; Zhe Tang; Asim Shahzad; Yaowei Luo; Xinyu Zeng; Zhifei Liang; Yangqing Wu; Lin Shu; Renbo Zhu; LinGe Wang (Chemical Engineering Journal, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Enhanced cycling and thermal stability of nickel-rich cathodes for lithium-ion batteries via molecular-weight-tuned polyaniline–polyethylene glycol interphase - Lin-Jie Xie; Jun-Cheng Jiang; Chen Liang; Qing-Song Wang; Hui-Qi Sun; Yan Tang; An-Chi Huang; Fei-Hao Zhu; Chi-Min Shu (Process Safety and Environmental Protection, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

APMAP regulated by YY1 transcription mediates ferroptosis and metastasis in non-small cell lung cancer through the PI3K/AKT/mTOR pathway - Xiaohong Zhuang; Shu Lin; Cheng-sheng zhang; Qi Qin; Qixing Yan; Jing-ru Luo; Wenjun Tang (Journal of Molecular Histology, 2026)

Psychromicrobium ferritrahens sp. nov., A Novel Actinobacterium Isolated from Decayed Wood in Shizong County, China - Lin-Bo Zhang; Jiang-Yuan Zhao; Yong-Jie Zeng; Hong-Bo Zha; Lin Gong; Pei-Wen Yang; Zhang-Gui Ding; Ming-Gang Li; Shun-Bo Gao; Le-Le Li; Shu-Kun Tang (Current Microbiology, 2026)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Hydrocarbon generation and pore evolution in marine organic-rich shales across maturation stages - Xueying Wang; Kun Zhang; Zhenxue Jiang; Yanhua Lin; Yan Song; Chengzao Jia; Shu Jiang; Lin Jiang; Hulin Niu; Jing Li; Yunbo Zhang; Xingmeng Wang; et al. (Fuel, 2025)

Urban-rural inequality in lung cancer risk from indoor air pollution: Prolonged indoor time amplifies the risks of solid fuel use - Ruimin Yang; Xinlin Mu; Guilian Wang; Deliang Tang; Bin Wang; Zhiwen Li; Haidong Kan; Nan Lin; Shu Tao (Journal of Environmental Management, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Microwave-extracted insect melanin as a metal chelator for bimetallic bioelectro-fenton cathodes: A sustainable approach to ibuprofen-contaminated wastewater treatment - Shu-Hui Liu; Hui-Yu Tang; Chi-Wen Lin; Wei-Jun Lai (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Females adapted better than males in Populus deltoides to simulated nitrogen deposition - Fang He; Shu-Ying Wei; Rui-Quan Wang; Jia Yao Tang; Peng Yang; Ting Wang; Jin-Liang Huang; Gang Chen; Tian-Tian Lin (Plant and Soil, 2025)

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Corrigendum to “Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella)” [Aquaculture Volume 598, 15 March 2025, 742053] - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Comparative analysis of three extraction methods for ginger leaf polysaccharide: Chemical composition, antioxidant activity, and hypolipidemic effects - Zhong-hao Zhang; Zhong-hua Zhao; Tian-yi Cao; Cai-rong Yang; Zi-zhong Tang; Shi-ling Feng; Shu Yuan; Sheng-lin Hu; Ming Yuan (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella) - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Cavity as radio telescope for galactic dark photon - Yanjie Zeng; Yuxin Liu; Chunlong Li; Yuxiang Liu; Bo Wang; Zhenxing Tang; Yuting Yang; Liwen Feng; Peng Sha; Zhenghui Mi; Weimin Pan; Tianzong Zhang; et al. (Science Bulletin, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Effects of pre-chlorination on ultrafiltration process in directly treating seasonal high-turbidity surface water: Membrane fouling control and shock load resisting - Haochun Wang; Yaru Zhang; Chenghai Lin; Ao Wang; Yanrui Wang; Yating Hu; Shu Jiang; Jinlong Wang; Heng Liang; Xiaobin Tang (Journal of Water Process Engineering, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Parathyroid hormone mediates the adverse impact of air pollution exposure on serum 25-hydroxyvitamin D: A nationwide cross-sectional study in China - Haitao Zhang; Jing Wang; Xia Meng; Bing Shu; Chunchun Yuan; Xingwen Xie; Zhangyu Liao; Xiaobing Jiang; Bolai Chen; Xinchao Lin; Xu Wei; Xiangyang Leng; et al. (Environmental Research, 2024)

Deciphering microbial metabolic interactions and their implications for community dynamics in acid mine drainage sediments - Shao-Ming Gao; Pandeng Wang; Qi Li; Wen-Sheng Shu; Ling-Yun Tang; Zhi-Liang Lin; Jin-Tian Li; Li-Nan Huang (Journal of Hazardous Materials, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Exploring the novel benefits of leucine: Protecting nitrite-induced liver damage in sub-adult grass carp (Ctenopharyngodon idella) through regulating mitochondria quality control - Lu-Lu Zhen; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Three species of rape responded to cadmium and melatonin alleviating Cd-toxicity in species-specific strategy - Xiao-long Qin; Yu-qing Zhao; De-jun Zhang; Ke-yu Wang; Wen-hui Chen; Zi-Zhong Tang; Yang-er Chen; Shu Yuan; Lin Ye; Ming Yuan (Environmental Pollution, 2024)

Positive feedback between the negative phase of interannual component of the Pacific Decadal Oscillation and La Niña - Hong-Shuo Tang; Yu Zhang; Yu Kosaka; Jun-Chao Yang; Qi Shu; Yi Liu; Xiaopei Lin (Climate Dynamics, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

The emerging role of zinc on alleviating inflammatory responses and enhancing immunity in grass carp (Ctenopharyngodon idella) - Xin Zeng; Zheng-Xing Song; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Juan Yang; Lin Feng (Aquaculture, 2024)

Selenium deficiency exacerbated Bisphenol A-induced intestinal toxicity in chickens: Apoptosis and cell cycle arrest mediated by ROS/P53 - Dongliu Luo; Xinyu Tang; Yixuan Wang; Shuqi Ying; Yujiao He; Hongjin Lin; Pervez Ahmed Khoso; Shu Li (Science of The Total Environment, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

The source of rock moisture in a sandstone cave in arid northern China: rainfall infiltration or vapor condensation? - Xiao-Wei Jiang; Kai-Gao Ouyang; Xu-Lin Tang; Shu-Cong Tan; Jia-Xin Shi; Na Li; Hong-Bin Yan; Jian-Guang Ren; Li Wan (Hydrogeology Journal, 2024)

Global change progressively increases foliar nitrogen–phosphorus ratios in China's subtropical forests - Yuan Lai; Songbo Tang; Hans Lambers; Peter Hietz; Wenguang Tang; Frank S. Gilliam; Xiankai Lu; Xianzhen Luo; Yutong Lin; Shu Wang; Feiyan Zeng; Qi Wang; et al. (Global Change Biology, 2024)
Globally increased nitrogen (N) to phosphorus (P) ratios (N/P) affect the structure and functioning of terrestrial ecosystems, but few studies have addressed the variation of foliar N/P over time in subtropical forests. Foliar N/P indicates N versus P limitation in terrestrial ecosystems. Quantifying long‐term dynamics of foliar N/P and their potential drivers is crucial for predicting nutrient status and functioning in forest ecosystems under global change. We detected temporal trends of foliar N/P, quantitatively estimated their potential drivers and their interaction between plant types (evergreen vs. deciduous and trees vs. shrubs), using 1811 herbarium specimens of 12 widely distributed species collected during 1920–2010 across China's subtropical forests. We found significant decreases in foliar P concentrations (23.1%) and increases in foliar N/P (21.2%). Foliar N/P increased more in evergreen species (22.9%) than in deciduous species (16.9%). Changes in atmospheric CO 2 concentrations (), atmospheric N deposition and mean annual temperature (MAT) dominantly contributed to the increased foliar N/P of evergreen species, while , MAT, and vapor pressure deficit, to that of deciduous species. Under future Shared Socioeconomic Pathway (SSP) scenarios, increasing MAT and would continuously increase more foliar N/P in deciduous species than in evergreen species, with more 12.9%, 17.7%, and 19.4% versus 6.1%, 7.9%, and 8.9% of magnitudes under the scenarios of SSP1‐2.6, SSP3‐7.0, and SSP5‐8.5, respectively. The results suggest that global change has intensified and will progressively aggravate N–P imbalance, further altering community composition and ecosystem functioning of subtropical forests.

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Monitoring and management of abandoned, lost and discarded fishing gear (ALDFG) in Penghu Islands, Taiwan - Wen-Hong Liu; Hung-An Chang; Hao-Tang Jhan; Chih-Cheng Lin; Li-Shu Chen; Chung-Lun Liu; Kuo-Huan Ting (Marine Pollution Bulletin, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Role of short-wave-sensitive 1 (sws1) in cone development and first feeding in larval zebrafish - Ke Lu; Xu-Fang Liang; Shu-Lin Tang; Jiaqi Wu; Lixin Zhang; Yuye Wang; Farui Chai (Fish Physiology and Biochemistry, 2023)

University-driven coastal partnerships to address ghost gear pollution: A case study in Penghu Islands of Taiwan - Chih-Cheng Lin; Kuo-Huan Ting; Hao-Tang Jhan; Chung-Lun Liu; Li-Shu Chen; Wen-Hong Liu (Marine Policy, 2023)

Isolation and characterization of an endophytic fungi from Zingiber officinale Rosc. and its activity to promote the growth of tissue culture ginger plantlets in bottles - Shuting Zhang; Yinghong Pei; Jiao Wang; Xiaolong Lin; Zizhong Tang; Lijun Zhou; Tao Chen; Shiling Feng; Chunbang Ding; Yanger Chen; Zhongwei Zhang; Shu Yuan; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Selenium Deficiency Induces Inflammatory Response and Decreased Antimicrobial Peptide Expression in Chicken Jejunum Through Oxidative Stress - Yujiao He; Lin Peng; Xiaochun Zhao; Xue Fan; Xinyu Tang; Guangliang Shi; Shu Li (Biological Trace Element Research, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Demographic characteristics of Cadra cautella on brown rice at different temperatures: Do diapausing individuals contribute to population growth rate? - Ya-Ying Lin; Cheng-Kang Tang; Pavel Saska; Ali Güncan; May-Chi Yao; Shu-Jen Tuan (Journal of Stored Products Research, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Selenium deficiency increased duodenal permeability and decreased expression of antimicrobial peptides by activating ROS/NF-κB signal pathway in chickens - He Yujiao; Tang Xinyu; Fan Xue; Li Zhe; Peng Lin; Shi Guangliang; Li Shu (BioMetals, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Transcriptome Analysis Provides an Overview of Genes Involved in the Peculiar Food Preference at First-Feeding Stage in Mandarin Fish (Siniperca chuatsi) - Ling Li; Shu-Lin Tang; Shan He; Xu-Fang Liang (Fishes, 2022)
The mandarin fish (Siniperca chuatsi) is an important economic fish species in China. Many carnivorous fish larvae feed on zooplankton or microdiets. However, the mandarin fish larvae feed on live prey fish exclusively, while refusing zooplankton or microdiets. A stable supply of palatable live prey fish results in high costs. Moreover, the application of live prey fish might bring the risk of pathogens. However, little is known about the genes underlying the food preference of mandarin fish larvae. Partial offspring of the domesticated strain could feed brine shrimp from three days post-hatching (dph), the open mouth day. In the present study, the mandarin fish larvae were randomly divided into three groups, then treated differently at 3 dph: (1) unfed; (2) fed with live prey fish; (3) fed with brine shrimp (Artemia). Differentially expressed genes were identified by RNA-seq. The differential expression of the transcription factors involved in retinal photoreceptor development and differentiation might contribute to the intake of brine shrimp in mandarin fish larvae. Meanwhile, the digestive enzyme genes involved in protein, fat, and carbohydrate digestion have been expressed in mandarin fish larvae at 3 dph, contributing to the digestion of ingested food. Our study provides an overview of genes and biological processes involved in the peculiar food preference at the first-feeding stage in mandarin fish larvae and has critical importance to the future application of non-fish live feeds in the culture of mandarin fish larvae.

Coupling Relationship of Geomorphic Evolution and Marine Hydrodynamics in the Stage-Specific Development of Urban Bays: A Modelling Case Study in Quanzhou Bay (1954–2017), China - Xianbiao Xiao; Yunhai Li; Junjian Tang; Fusheng Luo; Fangfang Shu; Liang Wang; Jia He; Xiaochun Zou; Wenqi Chi; Yuting Lin; Binxin Zheng (Journal of Marine Science and Engineering, 2022)
With the development of social economy and human activities, the geomorphology and hydrodynamic conditions of coasts have been dramatically changed, causing serious environmental pollution and resource depletion. Taking Quanzhou Bay as an example, this study combined geomorphologic change with a hydrodynamic model to simulate the change in tidal currents in different periods. The results show a change in the coastline was the main cause of hydrodynamic change during the industrialization reform. During the past 70 years, the tidal prism decreased year by year, and the average velocity of the tidal current in the channel decreased by 33.7% and 30.8% at flood and ebb tide, respectively. In the early stages of industrialization, reclamation land was used in a single way. The tidal prism decreased by 22.2% and 29.8% in the spring and neap tide, respectively. In the middle and later stages, the tidal current velocity increased, and reclamation land was used in a variety of ways. In modern society, the reclamation land-use type was unitary. Based on this research, we show the influence of human activities on the evolution of the bay’s geomorphology and provide suggestions for the management of the bay.

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Ocean Currents May Influence the Endolithic Bacterial Composition in Coral Skeletons - Po-Yu Liu; Sung-Yin Yang; Chih-Ying Lu; Naohisa Wada; Stéphane De Palmas; Shu-Shuo Yeh; Hideyuki Yamashiro; Sen-Lin Tang; Shan-Hua Yang (Frontiers in Marine Science, 2022)
Coral endolithic microbes can be an important nutrients support for hosts while under stresses. Previous studies have found that the endolithic microbial composition of a single coral species can be biogeographical diverse. However, the potential environmental factors, such as salinity, temperature, pH, and nutrient, that might influence the composition of the endolithic microbes remain unclear. In this study, we used both amplicon sequence variants (ASV) and a kmer-based taxonomic unit (KTU) to characterize the endolithic bacterial constitution of Isopora spp. located in the western Pacific Ocean—where it is subjected to the Kuroshio Current (in Okinawa, Japan and Green Island, Taiwan)—and the South China Sea (Dongsha Atoll). The endolithic bacterial community compositions showed a significant geographical difference, and we suggest that the ocean current and primary productivity are the most essential environmental factors influencing the bacterial communities in the skeleton of Isopora spp. In addition, our results showed that, technically, compared to ASV, bacterial composition based on KTU avoids extreme data, making it a suitable tool for explaining the associations between microbes and environmental factors.

Lentibacillus saliphilus. sp. nov., a moderately halophilic bacterium isolated from a saltern in Korea - Yun Wang; Gang-Qiang Jiang; Hong-Ping Lin; Peng Sun; Hong-Yan Zhang; Dong-Mei Lu; Li-Yun Wang; Chang-Jin Kim; Shu-Kun Tang (Archives of Microbiology, 2021)

Artificial Neural Network-based prediction of glacial debris flows in the ParlungZangbo Basin, southeastern Tibetan Plateau, China - Wang Tang; Hai-tao Ding; Ning-sheng Chen; Shang-Chang Ma; Li-hong Liu; Kang-lin Wu; Shu-feng Tian (Journal of Mountain Science, 2021)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Two new 5,6-epoxysterols from calcareous marine sponge Leucetta chagosensis - Wei-Zhuo Tang; Zhong-Zhen Yang; Fan Sun; Shu-Ping Wang; Fan Yang; Wei-Hua Jiao; Hou-Wen Lin (Natural Product Research, 2019)

Three new Coccomyces species from Shennongjia National Nature Reserve in China - Tu Lv; Wan-Peng Tang; Shu-Rui Cai; Cheng-Lin Hou (Mycological Progress, 2019)

Distinct evolutionary origins of common multi-drug resistance phenotypes in Salmonella typhimurium DT104: a convergent process for adaptation under stress - Le Tang; Song-Ling Zhu; Xin Fang; Yong-Guo Li; Cornelis Poppe; Randal N. Johnston; Gui-Rong Liu; Shu-Lin Liu (Molecular Genetics and Genomics, 2019)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

Gracilibacillus eburneus sp.nov., a moderately halophilic bacterium isolated from Xinjiang province, China - Hui-Lin Guan; Yun-Jiao Zhang; Xiao-Ju Lu; Man Jia; Zheng-Yun Zhang; Xu-Hong Gao; Yong-Chun Ma; Fei Tian; Shu-Kun Tang (Archives of Microbiology, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

Two new flavans from the roots of Dianella ensifolia (L.) DC - Ben-Qin Tang; Shu-Sheng Huang; Ye-Er Liang; Jian-Bo Sun; Yan Ma; Bao Zeng; Simon Ming-Yuen Lee; Jian-Lin Lu (Natural Product Research, 2017)

Characteristic of In Situ Stress and Its Control on the Coalbed Methane Reservoir Permeability in the Eastern Margin of the Ordos Basin, China - Junlong Zhao; Dazhen Tang; Hao Xu; Yong Li; Song Li; Shu Tao; Wenji Lin; Zhenxing Liu (Rock Mechanics and Rock Engineering, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

The roles of two transcription factors, ABI4 and CBFA, in ABA and plastid signalling and stress responses - Zhong-Wei Zhang; Ling-Yang Feng; Jian Cheng; He Tang; Fei Xu; Feng Zhu; Zhong-Yi Zhao; Ming Yuan; Yang-Er Chen; Jian-Hui Wang; Shu Yuan; Hong-Hui Lin (Plant Molecular Biology, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Effect of the CYP2C19*2 and *3 genotypes, ABCB1 C3435T and PON1 Q192R alleles on the pharmacodynamics and adverse clinical events of clopidogrel in Chinese people after percutaneous coronary intervention - Xiao-Fang Tang; Jing Wang; Jia-Hui Zhang; Xian-Min Meng; Bo Xu; Shu-Bin Qiao; Yong-Jian Wu; Jue Chen; Yuan Wu; Ji-Lin Chen; Run-Lin Gao; Jin-Qing Yuan; et al. (European Journal of Clinical Pharmacology, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

The effect of the red wine polyphenol resveratrol on a rat model of biliary obstructed cholestasis: involvement of anti-apoptotic signalling, mitochondrial biogenesis and the induction of autophagy - Tsu-Kung Lin; Li-Tung Huang; Ying-Hsien Huang; Mao-Meng Tiao; Kuo-Shu Tang; Chia-Wei Liou (Apoptosis, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

The 3Cs provide a novel concept of bacterial species: messages from the genome as illustrated by Salmonella - Le Tang; Shu-Lin Liu (Antonie van Leeuwenhoek, 2012)

New cytotoxic oxygenated sterols from marine bryozoan Bugula neritina - Fan Yang; Hong-Jun Zhang; Jian-Tao Chen; Hai-Feng Tang; Shu-Juan Piao; Wan-Sheng Chen; Hou-Wen Lin (Natural Product Research, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Rubellimicrobium roseum sp. nov., a Gram-negative bacterium isolated from the forest soil sample - Yan-Ru Cao; Yi Jiang; Qian Wang; Shu-Kun Tang; Wen-Xiang He; Quan-Hong Xue; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2010)

Streptomyces serianimatus sp. nov., isolated from a rhizophere soil - Yong-Xia Wang; Xiao-Yang Zhi; Hua-Hong Chen; Yu-Qin Zhang; Shu Kun Tang; Cheng-Lin Jiang; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2007)

Fiber type and myosin heavy chain compositions of adult pretarsal orbicularis oculi muscle - Nai-Chen Cheng; Shu-Lang Liao; I-Jong Wang; I-Chan Lin; Yueh-Bih Tang (Journal of Molecular Histology, 2007)

Streptomyces daliensis sp. nov. from soil - Ping Xu; Wen-Jun Li; Shu-Kun Tang; Hui-Ying Gao; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2006)